3,1-Benzothiazines, 1,4-Benzodioxines and 1,4-Benzoxazines as Inhibitors of Matriptase-2: Outcome of a Focused Screening Approach - Polya G. Roydeva; Anna-Madeleine Beckmann; Marit Stirnberg; Jožko Cesar; Danijel Kikelj; Janez Ilaš; Michael Gütschow (MDPI AG, 2016)
The liver enzyme matriptase-2 is a multi-domain, transmembrane serine protease with an extracellular, C-terminal catalytic domain. Synthetic low-molecular weight inhibitors of matriptase-2 have potential as therapeutics to treat iron overload syndromes, in particular in patients with β-thalassemia. A sub-library of 64 compounds was screened for matriptase-2 inhibition and several active compounds were identified. (S)-Ethyl 2-(benzyl(3-((4-carbamidoylphenoxy)methyl)-2,3-dihydrobenzo[b][1,4]dioxin-6-yl)amino)-2-oxoacetate ((S)-12) showed an IC50 value of less than 10 µM. Structure-activity relationships were discussed and proposals to design new matriptase-2 inhibitors were made.